Social Media Usage Behavior for Nursing Study after the COVID-19 Outbreak of Nursing Students at Princess of Naradhiwas University - Jarintanan, Punyisa; Waloh, Waenurmee; Nimu, Nisuraida (Princess of Naradhiwas University Journal, 2025)
The objective of this research was to examine the factors influencing nursing students' use of social media for their studies after the COVID-19 outbreak at Princess of Naradhiwas University. The study sample was composed of 220 nursing students from Princess of Naradhiwas University. The research tools included a personal information questionnaire, an internet usage pattern questionnaire, and a social media usage behavior of nursing students questionnaire. The reliability of the questionnaire was established at 0.90. Data were analyzed using descriptive statistics, and relationships were assessed using the Chi-Square Test. The findings revealed that the majority of students were female (89.1%). Students were categorized by year of study as follows: third year (31.4 %), second year (25.5 %), first year (21.8 %), and fourth year (21.3 %). The Grade Point Averages (GPAs) were predominantly good and very good, representing 59.1% and 33.6%, respectively. The highest average monthly income reported among the students was between 3,000 and 5,000 baht. Upon analyzing the relationships, it was found that personal factors such as gender, year of study, and monthly income were not significantly related to social media usage behavior for nursing studies. However, GPA was significantly related to social media usage behavior at a statistical level of 0.05. This indicates that students with good or very good academic performance tend to engage more with social media for their nursing studies compared to other groups. Therefore, it is recommended to provide better access to convenient and quality social media resources to support nursing education.